The effects of financial statement disaggregation on audit pricing. Issue 2 (4th November 2021) - Koh, Kevin; Tong, Yen H.; Zhu, Zinan
Abstract : We examine whether the extent of financial statement disaggregation affects the pricing of audit engagements in the United States. We hypothesize and find that auditors assess higher engagement risk and charge higher audit fees for clients with more disaggregated financial statements. We also find that these higher audit fees are not the result of either increased auditor effort to mitigate detection risk or heightened inherent and control risks reflected in lower financial reporting quality. Instead, we document that greater financial statement disaggregation is positively associated with litigation risk. This result suggests that higher audit fees arise out of auditors' assessments of heightened client and auditor business risks associated with litigation. While financial statement disaggregation may have beneficial effects on the quality of financial information, we document that financial statement disaggregation can impose costs on firms in terms of higher audit fees and a higher likelihood of litigation. Our study informs standard setters, firms and auditors as they debate the costs, benefits and extent of disaggregation to be presented in financial statements.